Variability of early autumn planktonic assemblages in the strait of Gibraltar: a regionalization analysis - VALCÁRCEL-PÉREZ, NEREA; RAMÍREZ-ROMERO, EDUARDO; GARCÍA, CARLOS M.; GONZÁLEZ-GORDILLO, JUAN IGNACIO; ECHEVARRÍA, FIDEL (Mediterranean Marine Science, 2022)
The Strait of Gibraltar (SG) is the only connection of the Mediterranean Sea with the global circulation. The SG is an outstanding marine region to explore physical-biological coupling of pelagic communities due to its hydrodynamic complexity, including strong tidal forcing and marked spatial gradients and fronts. The authors have unravelled the role of the fortnightly tidal scale (spring and neap tides) and local processes (upwelling and tidal-topographic mixing) that shape planktonic assemblages in the Strait. To do so, an oceanographic cruise was taken in early autumn 2008 with a high-resolution grid sampling and spring/neap tidal conditions. The planktonic features were captured using different automatic and semi-automatic techniques of plankton analyses (flow cytometry, FlowCAM, LOPC and Ecotaxa) that allowed covering a wide range of sizes of the community from pico- to mesoplankton. The SG was sectorized into two clusters based on the biogeochemical and main water column properties. Cluster 1 (CL1) covered shallow productive areas around Cape Trafalgar (CT). CL1 presented higher concentrations of chlorophyll and nutrients, and phytoplankton was mostly represented by Synechococcus and coastal diatoms while zooplankton had the highest percentage of meroplankton (31%). In contrast, cluster 2 (CL2) covered open ocean waters and presented more oligotrophic features, i.e. nitrogen-depleted waters with lower chlorophyll concentrations and a picoplankton community dominated by Prochlorococcus and holoplankton predominance in mesozooplankton. Under early autumn conditions with overall nutrient-depleted and stratified waters, the CT area emerges as an ecosystem where the constant tidal mixing and nutrients supply is coupled with an active production also being favored by high residence times and finally shaping a plankton community with unique features in the area.